2004
DOI: 10.1093/annhyg/meg077
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Standardized Chipping Hammer Test Specified in ISO 8662-2

Abstract: The measurement method has a good repeatability except at a high feed force. The feed force has a significant effect on the vibration emission. The single feed force specified in the standard may not be sufficient to test the tool behaviors. Multiple levels of feed force should be used for the chipping hammer test. Doing so may provide a more appropriate basis for tool screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…A coherence analysis of the triaxial vibrations was carried out using the vibration data measured in our previous studies on many powered hand tools such as grinders, sanders, chipping hammers, jack hammers, riveting hammers, impact wrenches and vibrating forks (Dong et al, “Evaluation of the Standardized Chipping Hammer Test,” 2004; McDowell et al 2008, 2009, 2012, 2013). The analysis found that the coherence values at the dominant vibration frequencies of these tools generally fall in the range of 0.5–0.9.…”
Section: Resultsmentioning
confidence: 99%
“…A coherence analysis of the triaxial vibrations was carried out using the vibration data measured in our previous studies on many powered hand tools such as grinders, sanders, chipping hammers, jack hammers, riveting hammers, impact wrenches and vibrating forks (Dong et al, “Evaluation of the Standardized Chipping Hammer Test,” 2004; McDowell et al 2008, 2009, 2012, 2013). The analysis found that the coherence values at the dominant vibration frequencies of these tools generally fall in the range of 0.5–0.9.…”
Section: Resultsmentioning
confidence: 99%
“…In the cases of large tools such as chipping hammers, road breakers, and rock drills, additional grip force may also be applied to increase the stability of the adapter. While increasing the push/feed force could change the tool vibrations [40], the increased grip force is unlikely to significantly change the vibrations of these tools.Apply vibration transmissibility spectra measured in laboratory human subject tests as correction factors for reducing measurement errors. The glove-induced errors in the palm adapter method and the glove-held adapter method are systematic and measurable in laboratory human subject tests.…”
Section: Discussionmentioning
confidence: 99%
“…In the cases of large tools such as chipping hammers, road breakers, and rock drills, additional grip force may also be applied to increase the stability of the adapter. While increasing the push/feed force could change the tool vibrations [40], the increased grip force is unlikely to significantly change the vibrations of these tools.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a layer of synthetic rubber was used as a mechanical filter to minimize or eliminate the DC shift. This synthetic rubber layering technique has been proven to be successful in several earlier experiments involving impact tools (Dong et al, 2004; McDowell et al, 2009, 2012). The effectiveness of this accelerometer installation technique was verified in the previous NIOSH bucking bar study by conducting a series of simultaneous vibration data collection trials with each bucking bar using a laser vibrometer along with the installed accelerometers (McDowell et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Dong et al (2005) found that the push force, or feed force, has a more pronounced effect on the hand-arm system biodynamic response than does grip force. Feed force has also been shown to be a significant factor in measurements of tool vibrations during standardized vibration assessments of percussive tools (Dong et al, 2004).…”
Section: Introductionmentioning
confidence: 99%